New polyketides and new benzoic acid derivatives from the marine sponge-associated fungus Neosartorya quadricincta KUFA 0081 - Prompanya C. (2016)
Two new pentaketides, including a new benzofuran-1-one derivative (1) and a new isochromen-1-one (5), and seven new benzoic acid derivatives, including two new benzopyran derivatives (2a, b), a new benzoxepine derivative (3), two new chromen-4-one derivatives (4b, 7) and two new benzofuran derivatives (6a, b), were isolated, together with the previously reported 2,3-dihydro-6-hydroxy-2,2-dimethyl-4H-1-benzopyran-4-one (4a), from the culture of the marine sponge-associated fungus Neosartorya quadricincta KUFA 0081. The structures of the new compounds were established based on 1D and 2D NMR spectral analysis, and in the case of compounds 1, 2a, 4b, 5, 6a and 7, the absolute configurations of their stereogenic carbons were determined by an X-ray crystallographic analysis. None of the isolated compounds were active in the tests for antibacterial activity against Gram-positive and Gram-negative bacteria, as well as multidrug-resistant isolates from the environment (MIC > 256 μg/mL), antifungal activity against yeast (Candida albicans ATTC 10231), filamentous fungus (Aspergillus fumigatus ATTC 46645) and dermatophyte (Trichophyton rubrum FF5) (MIC > 512 μg/mL) and in vitro growth inhibitory activity against the MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer) and A375-C5 (melanoma) cell lines (GI50 > 150 μM) by the protein binding dye SRB method. © 2016 by the authors; licensee MDPI.